Wave propagation and scattering in elastic plate with periodically grooved surface - DANICKI, E.; BOGUCKI, D. (Archives of Acoustics, 1993)
Bragg reflection of plate waves in isotropic elastic plate with a periodically grooved surface is analyzed. Mode-coupling effect is also taken into account. The analysed problem may be applied in the construction of piezoelectric resonators and RAC filters.